2016
DOI: 10.3892/ijo.2016.3352
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic mechanism of PLK1 inhibitor GSK461364 against osteosarcoma: Mitotic arrest, apoptosis, cellular senescence, and synergistic effect with paclitaxel

Abstract: Abstract. Polo-like kinase 1 (PLK1), a serine/threonine kinase and an oncogene, is crucial in regulating cell cycle progression. PLK1 also has been demonstrated as a potential target of osteosarcoma (OS) by using short hairpin RNA libraries in lentiviral vectors for screening of protein kinase. In preclinical studies, GSK461364, a potent and selective ATP-competitive PLK1 inhibitor, showed antiproliferative activity against multiple tumor cell lines. In the present study, we evaluated the expression level of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 41 publications
4
18
0
Order By: Relevance
“…STK899704 treatment increased p53, phosphorylated p53, p21, and p27 levels ( Figure 5A ), which may be due to the decrease in cyclin A level and G 2 /M phase arrest because of tubulin aggregation. These data supported already reported results regarding on the causes of senescence ( Roninson et al, 2001 ; Tierno et al, 2009 ; Chou et al, 2016 ). Also, β-Galactosidase staining showed that STK899704 induced senescence in A549 cells compared with that in control cells.…”
Section: Discussionsupporting
confidence: 93%
“…STK899704 treatment increased p53, phosphorylated p53, p21, and p27 levels ( Figure 5A ), which may be due to the decrease in cyclin A level and G 2 /M phase arrest because of tubulin aggregation. These data supported already reported results regarding on the causes of senescence ( Roninson et al, 2001 ; Tierno et al, 2009 ; Chou et al, 2016 ). Also, β-Galactosidase staining showed that STK899704 induced senescence in A549 cells compared with that in control cells.…”
Section: Discussionsupporting
confidence: 93%
“…We tried to elucidate the underlying molecular mechanisms of the synergism of PLK1 inhibitors with paclitaxel and found that the combined treatment causes strong growth inhibition and mitotic arrest, which triggers activation of caspase-3 and apoptosis; these results correlate with previous findings [36,41]. Recently, Noack et al identified a synthetic lethality between volasertib and paclitaxel in ovarian cancer cell lines with CCNE1-amplification, demonstrating that the combination induces a prolonged mitotic arrest and cell death, shifting the balance between pro-and anti-apoptotic proteins toward cell death [42].…”
Section: Discussionsupporting
confidence: 73%
“…A number of studies have shown that inhibiting PLK1 expression or function by RNAi or small molecule inhibitors was effective in control of cancer cell proliferation [38], [50], [108], [109].…”
Section: Plk1 and Human Cancermentioning
confidence: 99%